Evaluation of a novel method to calculate cementless femoral stem level on craniocaudal projection radiographs. Issue 8 (20th September 2021) - Brand, Kenneth J.; Beale, Brian S.; Hudson, Caleb C.
Abstract: Objective: To assess the accuracy of a proportion‐corrected radiographic cementless femoral stem level calculation in a cadaver model. Study design: Cadaveric study. Sample population: Twelve cadaveric canine femurs. Methods: Cementless femoral stems were implanted in 12 cadaver femurs at three stem levels. Craniocaudal projection radiographs of the implanted femurs were obtained at 0°, 10°, 20°, 30°, and 45° angulations in the sagittal plane (relative to the radiographic plate) and at 0°, 15°, and 30° internal and external axial rotation. A proportional calculation including actual stem length, radiographically measured stem length, and radiographically measured stem level relative to the greater trochanter (uncorrected stem level) was solved to yield a corrected stem level. The errors of the stem level measurements were compared. Results: With 0° or 15° of internal rotation, the true stem level differed by more than 0.5 mm from corrected stem level in 2 of 30 tested femoral positions. It differed from the uncorrected stem level in 10 of 30 positions. With 15° and 30° external rotation or 30° internal rotation, the corrected stem level was not more accurate than the uncorrected stem level for any femoral position. Conclusion: Use of a proportion correction minimized variability in the stem‐level measurements due to sagittal angulation (up to 30°) of the femur at 0° or 15° of internal rotation. Clinical significance: A proportion correction can improve the accuracy of femoral stem‐level assessment on craniocaudal projection radiographs, which may aid in the detection of subsidence after cementless total hip replacement.